Migration theory : talking across disciplines - Brettell, Caroline; Hollifield, James Frank, 1954- (New York : Routledge, 2015)
'During the last decade the issue of migration has increased in global prominence and has caused controversy among the host countries around the world. Continuing their interdisciplinary approach, editors Caroline Brettell and James Hollifield have included revised essays from the previous edition of Migration Theory in such fields as anthropology, political science, law, demography, and geography, as well as new essays focusing on history, economics, and sociology. Each chapter is international in scope. Chapter authors also cross-reference other chapters, indicating the differences across disciplines as well as exploring similarities. Returning authors have revised their chapters to encompass changes in their field. New authors will offer a fresh approach to the disciplinary perspectives. Scholars and students in migration studies will find this book a powerful theoretical guide and a text that brings them up to speed quickly on the important issues and the debates. All of the social science disciplines will find that this book offers a one-stop synthesis of contemporary thought on migration.'--
Includes bibliographical references and index.
Keywords: Emigration and immigration